LEGAL RESPONSIBILITY FOR USING OIL FUEL ON PARTALITE DEFENSE (CASE STUDY OF DITPOLAIRUD POLDA BALI) - Arimbhawa, I Gusti Kade; Nurianto, Nurianto; Damanik, Siti Nurmawan (International Journal of Social Service and Research, 2024)
The purpose of this study is to find out and analyze legal accountability and factors that affect perpetrators in the misuse of Pertalite Assignment Fuel Oil. In a five-year period, from 2019 to 2023, the Bali Regional Police Directorate handled 10 cases of misuse of Oil and Gas Fuel. The authors conclude that the absence of regulation regarding the maximum limit for the purchase of special assignment fuel with jerry cans, thus causing the Blurring of Legal Norms, so that this can cause the abuse of fuel oil. Factors such as low legal awareness and public compliance with the rules, the dominance of individual and group interests, and the lack of knowledge about applicable regulations are the main causes of the misuse.